Muhkam: Nilai Pendidikan Akhlak dalam Alquran - Mar’atus Solihah; M. Iqbal Irham (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2022)
The issue of moral education is widely discussed in various books and articles, which makes this issue a trending topic of discussion. Concepts and discussions about this issue also vary, depending on the angle from which this problem is viewed. This study examines the value of moral education in the Qur'an. This study focuses on the verse of Muhkam in the Qur'an surah Al-Isra’ which aims to find out how the value of moral education is contained in the verse of Muhkam. This research is a literature study that uses the Qur'an as primary data. The secondary data were taken from various Quran interpretation books and other supporting books and articles related to the value of moral education. This study uses content analysis and uses a thematic interpretation approach (maudhu'i). The results of this study are the value of moral education which includes how to have morals towards God, morals towards others, and morals towards self.